Recurrent Variceal Bleeding Due to Non-Cirrhotic Portal Hypertension in a Patient with Primary Myelofibrosis: Case Report - Sitorus, Debora; Anwar, Bariani; Dinakrisma, Anastasia Asylia (The Indonesian Society for Digestive Endoscopy, 2025)
Acute upper gastrointestinal bleeding may arise from variceal or non-variceal sources. Primary myelofibrosis, classified as a subtype of myeloproliferative neoplasms, represents an uncommon clinically significant etiology of non-cirrhotic portal hypertension. The authors reported a case of a 39-year-old woman with recurrent variceal bleeding for six years. She presented with progressive weight loss, splenomegaly, and severe anemia. One year before her first episode of hematemesis, a bone marrow biopsy revealed myelofibrosis grade 2, and JAK2 V617F mutation was positive, confirming primary myelofibrosis. The treatment was discontinued due to high expense. Abdominal ultrasonography showed portal hypertension and changes suggestive of cirrhosis. She underwent successful endoscopic variceal ligation to control active bleeding, and initiation of a JAK inhibitor (ruxolitinib) was recommended for outpatient management to address the underlying disease. This case highlights that in patients presenting with variceal bleeding and portal hypertension in the absence of cirrhosis, myeloproliferative neoplasms, such as primary myelofibrosis should be considered as a differential diagnosis. This study aimed to raise awareness of primary myelofibrosis as a rare cause of non-cirrhotic portal hypertension and emphasize the importance of early recognition and targeted therapy to prevent recurrent bleeding and disease progression.